Reducing Vulnerability of Somali Communities by Raising the Capacity of Indigenous Systems and Enhancing Market Access and Consumer Welfare: Knowledge of livestock grading and market participation among small ruminant producers in northern Somalia - Mtimet, Nadhem; Wanyoike, Francis; Mugunieri, Lawrence; Ndiwa, Nicholas; Warsame, Ahmed; Marshall, Karen (International Livestock Research Institute, 2023)
This activity focused on market participation and producer's knowledge of the indigenous livestock grading and pricing system applied to small ruminant marketing in Somaliland. Data were collected from a random sample of 143 men and women producers in three livelihood zones: Hawd pastoral, West Golis pastoral and Togdheer agro-pastoral zones. Descriptive statistics (means and frequencies) were used to evaluate the level of awareness about the grading system and also to investigate whether the producers made any deliberate efforts to exploit the grading system for higher returns. A Heckman (1979) two stagemodel was used to evaluate the effect of producers' knowledge of the indigenous livestock grading system and other factors on market participation. , The overall objective of this project is to contribute to Somalia's pro-poor livestock development. This project contributes to reduced vulnerability of pastoral communities by strengthening the use of indigenous resources and increasing market access. The overall objective will be achieved by (1) enhancing local capacity to access indigenous and other knowledge on Somali livestock and mobilize it for decision-makers and (2) engaging industry and government in improving the marketing and safety of livestock products. The project focuses on institutions that enable the gains from improved trade to be better utilized in producer and consumer welfare, and in furthering the interests of women. Private-sector organizations that have emerged as the institutional drivers of the Somali economy will be assisted to provide governance. Their participation in building institutions (knowledge transfer and product standards) is compatible with private incentives and with the public roles of oversight and audit. Specific objectives The specific objectives of the project are to: Compile indigenous knowledge and information on Somali livestock, Strengthen professional capacities for classification, standardization and dissemination of knowledge and information about Somali livestock.